Effects of Obesity on Axillary Lymph Node Structure: Association of Hilar Fat Deposition and Alterations in Cortex Width - KESHAVARZ, Elham (Maedica (Bucur), 2020)
Introduction: This study aims to evaluate the effects of obesity on the structure of axillary lymph nodes in women with no evidence of breast or axilla pathology. Method: In this prospective study, we documented the body mass index of 204 women who were referred for screening mammography. Two radiologists have independently viewed the mammograms to find the largest axillary lymph node and reported its dimensions. Independent sample T-test was used to evaluate the association of the above indices with participants’ body mass index. Associations between indices were investigated using multiple regression analyses. Results: All measurements of axillary lymph nodes and hilo-cortical ratio were significantly increased with increasing body mass index (p<0.001), except for cortex width (p=0.15). There were strong associations (p < 0.001) between increasing hilum length and increasing lymph node length (R²=0.90), increasing hilum width and increasing lymph node width (R²=0.85), and increasing hilum width and decreasing cortex width (R²=0.12). There was no association between cortex width and lymph node width (R²=0.0001). Inter-rater reliability ranged from 0.49 to 0.70. Conclusion: Our study demonstrated that axillary lymph nodes with a bigger hilum width had a smaller cortex width in obese but apparently normal population. Considering the important role of axillary lymph node cortex in their immune function, this may be a cause for immune dysfunction of axillary lymph nodes in obesity and explain the worse prognosis of breast cancer in obese women. The limited number of participants, the 2-dimensional nature of mammograms and the difficulty of measuring the dimensions of axillary lymph nodes using mammography were important limitations of this study. Implications for practice: Obesity may result in structural change and dysfunction of axillary lymph nodes. Dysfunction of axillary lymph nodes may have a role in worse prognosis of breast cancer in obese patients.